Kredyt rolniczy w Polsce w warunkach członkostwa w Unii Europejskiej - Daniłowska, Alina (Agricultural Credit in Poland in Conditions of Its Membership in the European Union, 2005)
The aim of the paper is to analyse the role of agricultural credit during the first months of the Polish membership in EU. Before the accession and during the first period of the membership in UE Polish farmers were offered many forms of support but it seems that credit support system will still remain important in some next years.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 143-148